Mental health and psychosocial support among refugee children and adolescents with HIV in West Nile Uganda: An exploratory study - Molly Naisanga; Emmanuel Mpamizo; Noeline Nakasujja (PLOS Global Public Health, 2026)
Refugee populations face disruptions in social services, particularly HIV- related care such as access to Highly Active Antiretroviral Therapy. Uganda hosts the highest number of refugees in Africa. These children and adolescents (CAs) are faced with several mental health and psychosocial challenges that are amplified by their humanitarian context. Multiple health and social welfare partners support Children and Adolescents with HIV (CA-HIV) in overcoming these challenges. However, no clear documentation exists on the mental health and psychosocial support (MHPSS) services available to aid the care-seeking process and design. We therefore set out to explore MHPSS services for CA-HIV in the refugee settlements of West Nile, Uganda. This study utilized an exploratory-descriptive qualitative approach. Participants included CA-HIV, their caretakers and people involved in offering MHPSS services to them. Altogether, we conducted 4 in-depth interviews and 9 focus group discussions. Study participants were recruited from refugee settlements in West Nile, Uganda and were invited to participate in focus group discussions, key informant interviews and in-depth interviews. The proceedings from these discussions and interviews were audio recorded, transcribed, and translated to English when necessary. Analysis by inductive thematic analysis was done using NVivo software. Three key themes emerged: Perceptions and markers of mental unwellness (including etiology, signs and symptoms), MHPSS and its related challenges among refugee CA-HIV (arising due to both the HIV serostatus and refugee status of the CA) and the role of the self, specialized and non-specialized service providers towards the MHPSS wellbeing of this population. MHPSS markers, challenges and interventions are multifaceted. The interventions involve specialized personnel, non-specialized personnel and the children themselves. All these ought to be carefully considered as we seek to address the contextual MHPSS challenges faced by refugee CA-HIV.